Gender and access to justice in Burundi: conflicting norms, gaps in the law and the role of judges. Issue 3 (2nd September 2021) - Niyonkuru, Aimé-Parfait
ABSTRACT: Like many other African countries, Burundi has a pluralistic legal system, where on the one hand written laws coexist with uncodified customary laws and on the other hand informal justice institutions are still used in the day-to-day conflict resolution by many Burundians despite a provision in the Constitution that makes the mission of rendering justice the monopoly of the state courts. Both before the state courts and out-of-court forums for adjudicating disputes and justice mechanisms, women face challenges that limit their access to justice, compared to men. This paper argues three main points. First, that while there is a relationship between women's limited access to justice and the pluralistic nature of Burundi's legal system, the challenges faced by women in accessing justice should not be excessively associated with legal pluralism, thus hiding the impact of extra-legal factors. Second, that while Burundi's constitutional framework is progressive with respect to gender equality and most laws are gender neutral, some shortcomings still exist in the overall legal framework, thus limiting the potential of the constitutional legal framework with respect to gender equality. Third, that by increasing gender diversity in the judiciary, and with much more positive activism and training, Burundian judges could ensure equal access to justice for women by using the potential of existing national and international legal frameworks.